Dermatomyositis - Dourmishev, Lyubomir (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Background: The pathogenesis of the inflammatory processes in the skin of dermatomyositis patients remains unclear. The aim of this study was to investigate the patterns of proliferation and apoptosis of epidermal keratinocytes and dermal infiltrating cells in DM patients. Material and methods: Seventeen skin biopsy specimens from patients with dermatomyositis, which fulfiiled the diagnostic criteria of Bohan and Peter, and Euwer and Sontheimer, were immunohistochemically investigated with monoclonal antibodiesagainst human Ki-67, Bcl-2, CD3, CD4, anti-CD 45R0 and a reaction was detected by streptovidine-biotin complex (Uni-Pak ABC). Results: The lesional skin showed a marked increase of Ki-67-positive keratinocytes, which were predominantly located in the basal and germinative layer, but a lack of cells in areas of vacuolar degeneration and epidermal atrophy. A drastic reduction in the number of Bcl-2-positive cells localized in the basal cell compartment was observed. Antigen activated T lymphocytes (CD 45R0+) and CD3+ cells were in higher prevalence in dermal perivascular infiltrates of the affected skin. Conclusion: The defective regulation of apoptosis may play an important role in the development of cutaneous lesions of patients with dermatomyositis, in which the skin is a prominent target organ. Abnormal expression of Ki-67 and diminution of Bcl-2 in the epidermis, coupled with theperivascular location of T cells in the dermis are crucial keys to the histological diagnosis of dermatomyositis.
Keywords: Biopsija; Biopsy; dermatologija; Dermatomiozitis; Dermatomyositis; histopatologija; Immunohistochemistry; Imunohistokemija; Ki-67 Antigen; limfociti; Limfociti T; Pathology; Proto-Oncogene Proteins C-Bcl-2; Proto-onkogene beljakovine c-bcl-2; T-Lymphocytes